Penerapan Aplikasi Blank Map Puzzle sebagai Media Pembelajaran Geografi Siswa Kelas XII IPS di SMA Negeri Titian Teras Jambi - Adrianto, Moch Dimas Fariz; Nofrion, Nofrion (Lembaga Yasin AlSys, 2026)
This study aims to describe the implementation of the blank map puzzle application as a geography learning medium for Grade XII IPS students at SMA Negeri Titian Teras Jambi and the learning outcomes achieved by the students. The study employs a quantitative approach with an experimental method and a control group pretest–posttest design. The research population comprises all Grade XII IPS students at SMA Negeri Titian Teras Jambi, with Grade XII F-4 students serving as the experimental class and Grade XII F-1 students as the control class. Based on the data analysis, the average geography learning outcomes of students in the experimental class using the blank map puzzle application as a learning medium are higher than those of the control class using conventional media. In addition, there is a difference in learning outcomes between students who follow geography instruction using the blank map puzzle application and those who learn using conventional media. Thus, the implementation of the blank map puzzle application as a geography learning medium is shown to influence students’ learning outcomes.